2020
DOI: 10.3389/fcell.2020.561179
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Exerts Neuroprotective Effects in β-Amyloid-Treated SH-SY5Y Cells Through the Regulation of Heme Oxygenase-1: Novel Insights for an Old Drug

Abstract: The formation and aggregation of amyloid-β-peptide (Aβ) into soluble and insoluble species represent the pathological hallmarks of Alzheimer’s disease (AD). Over the last few years, however, soluble Aβ (sAβ) prevailed over fibrillar Aβ (fAβ) as determinant of neurotoxicity. One of the main therapeutic strategies for challenging neurodegeneration is to fight against neuroinflammation and prevent free radical-induced damage: in this light, the heme oxygenase/biliverdin reductase (HO/BVR) system is considered a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“… 26 Celecoxib NSAID Osteoarthritis, Rheumatoid arthritis PTGS2, PDPK1, CDH11 + + + Mhillaj et al. 27 Mifepristone Hormone modulators Early pregnancy termination PGR, NR3C1, KLK3 + Pomara et al. 28 Trazodone Antidepressants Major depressive disorder HTR2A, HTR2C, SLC6A4 + + Ashford 29 Ibuprofen NSAID Pain, Osteoarthritis, Rheumatoid arthritis COX-1, COX-2, PTGS2 + + + Van Dam 30 Avagacestat (BMS-708163) Anti-amyloid NA γ-secretase + Tong et al.…”
Section: Resultsmentioning
confidence: 99%
“… 26 Celecoxib NSAID Osteoarthritis, Rheumatoid arthritis PTGS2, PDPK1, CDH11 + + + Mhillaj et al. 27 Mifepristone Hormone modulators Early pregnancy termination PGR, NR3C1, KLK3 + Pomara et al. 28 Trazodone Antidepressants Major depressive disorder HTR2A, HTR2C, SLC6A4 + + Ashford 29 Ibuprofen NSAID Pain, Osteoarthritis, Rheumatoid arthritis COX-1, COX-2, PTGS2 + + + Van Dam 30 Avagacestat (BMS-708163) Anti-amyloid NA γ-secretase + Tong et al.…”
Section: Resultsmentioning
confidence: 99%
“…Results reported by Mhillaj et al, confirmed CO and Bilirubin ability to reduce ROS formation induced by soluble amyloid-β-peptide and fibrillar amyloid-β-peptide, and demonstrated the capacity of CO and bilirubin to reduce growth rate of Aβ oligomers in AD [ 131 ].…”
Section: Contribution Of Ho-1 Induction In Pathological Conditionsmentioning
confidence: 90%
“…Evidence indicated that Nrf2 inhibited the microglial activation and thereby suppressed neuronal loss. 31 Furthermore, HO-1 also plays a vital role in the inflammatory response via the release of the anti-inflammatory gaseous molecule CO. 32 There is a crosstalk between Nrf2 and NFκB, and the balance between them is essential in the precession of neurodegenerative disease because these two molecules direct the opposite genes. 6 Glutamate also leads to inflammatory response, and thus, we checked whether WCPFSRSF regulated the NFκB pathway (Figure 5A).…”
Section: ■ Discussionmentioning
confidence: 99%